Identification of a novel HLA‐B allele, B*46:39, by sequence‐based typing. Issue 5 (16th October 2013) - Son, J. A.; Lee, J. Y.; Oh, S. H.; Shin, J. H; Kim, H. R.
<x xml:space="preserve">Abstract</x> The new allele B*46:39 showed a single‐nucleotide substitution compared with B*46:01 at codon 185 (CCA/ACA).